Burkina Faso : Selected Issues and Statistical Annex. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper and Statistical Annex analyzes the cotton sector in Burkina Faso. The paper highlights that the effect of the sharp drop in international prices of cotton since mid-2001 was much better managed in Burkina Faso than in most of the neighboring cotton-producing countries. The reforms implemented in the cotton sector since 1998 are summarized. The paper also emphasizes that this reform process has been successful is securing and expanding cotton production in Burkina Faso.